PENGARUH MODEL PEMBELAJARAN PROJECT CITIZEN TERHADAP PARTISIPASI AKTIF SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA SD NEGERI 53 BANYORANG KABUPATEN BANTAENG - Nadwah, Nadia; Aeni Rahman, Syarifah; Irma Suriani, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Project Citizen learning model on students' active participation in Pancasila Education subject at SD Negeri 53 Banyorang, Bantaeng Regency. This research used a quantitative approach with a pre-experimental design using one-group pretest-posttest design. The subjects were 22 fifth-grade students consisting of 11 male and 11 female students. Data were collected through questionnaires and observation sheets. The results showed that before the treatment, 63.64% of students were in the Less Active category and 36.36% were in the Moderately Active category. After implementing the Project Citizen model, 50% of students were in the Very Active category and 50% in the Active category. The paired samples t-test showed t = -19.205 with p < 0.001, indicating a highly significant effect with an average increase of 99.53%. Cohen's d effect size yielded d = 6.226 (huge effect, d > 2.0), demonstrating a very large practical influence. It is concluded that the Project Citizen learning model significantly affects students' active participation through improvements in the indicators of giving opinions, giving responses, doing assignments, and concluding learning material.